Expression, purification, crystallization and preliminary X-ray analysis of Plasmodium falciparum GTP:AMP phosphotransferase - Law, Alan W. L. (2013)
Adenylate kinases (AKs) are phosphotransferase enzymes that catalyze the interconversion of adenine nucleotides, thereby playing an important role in energy metabolism. In Plasmodium falciparum, three AK isoforms, namely PfAK1, PfAK2 and GTP:AMP phosphotransferase (PfGAK), have been identified. While PfAK1 and PfAK2 catalyse the conversion of ATP and AMP to two molecules of ADP, PfGAK exhibits a substrate preference for GTP and AMP and does not accept ATP as a substrate. PfGAK was cloned and expressed in Escherichia coli and purified using two-step chromatography. Brown hexagonal crystals of PfGAK were obtained and a preliminary diffraction analysis was performed. X-ray diffraction data for a single PfGAK crystal were processed to 2.9 Å resolution in space group P3121 or P3221, with unit-cell parameters a = b = 123.49, c = 180.82 Å, α = β = 90, γ = 120°.